Trust no one : a thriller - Rollins, James, 1961- (William Morrow, an imprint of HarperCollins Publishers, 2026)
"The ritualistic murder of a British professor at the University of Exeter points to his own students. All evidence points to Sharyn Karr--an American student. Prior to the professor's death, he had thrust a centuries-old book upon her. It appears to be the handwritten and encrypted diary of an eighteenth-century mystic and occultist, the Comte de Saint-Germain. The professor begged her to keep the text safe, ending with a warning: Trust no one. Such a responsibility forces her into cooperation with Duncan Maxwell, a fellow postgrad and the sixteenth in line to the British Crown. Already, Duncan has proven himself a savant with encryptions. Unfortunately, the pair clash at every level, but they both need one another. Especially when they discover the book's opening words: Herein lies the secret to my immortality. Come find me, if you dare ... "--Publisher description.